2009
DOI: 10.1590/s1517-83822009000100023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fumonisin producing Fusarium verticillioides in paddy (Oryza sativa L.) using polymerase chain reaction (PCR)

Abstract: The study reports the occurrence of fumonisin producing Fusarium verticillioides in 90 samples of stored paddy (Oryza sativa L.) collected from different geographical regions of Karnataka, India. Fumonisin producing F. verticillioides was identified based on micromorphological characteristics and PCR using two sets of primers. One set of primers was F. verticillioides species specific, which selectively amplified the intergenic space region of rDNA. The other set of primers was specific to fumonisin producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Of the five species of Fusarium isolated in this study, four, namely F. proliferatum, F. verticillioides, F. chlamydosporum and Fusarium sp., were shown in this mycological study to be mycotoxigenic producing FB, ZEA, DON and T-2 on YES. F. proliferatum and F. verticillioides, which were shown herein as producers of FB1 and FB2, are not only important toxin-producing fungi associated with maize worldwide (Dutton 1996;Kpodo et al 2000;Marasas 2001), but have been isolated from other food commodities (Reddy et al 2006) including rice (Pitt and Hocking 1997;Pacin et al 2002;Makun et al 2007;Maheshwar et al 2009). In fact, Park et al (2005) found F. proliferatum as the most frequent Fusarium spp.…”
Section: Discussionmentioning
confidence: 86%
“…Of the five species of Fusarium isolated in this study, four, namely F. proliferatum, F. verticillioides, F. chlamydosporum and Fusarium sp., were shown in this mycological study to be mycotoxigenic producing FB, ZEA, DON and T-2 on YES. F. proliferatum and F. verticillioides, which were shown herein as producers of FB1 and FB2, are not only important toxin-producing fungi associated with maize worldwide (Dutton 1996;Kpodo et al 2000;Marasas 2001), but have been isolated from other food commodities (Reddy et al 2006) including rice (Pitt and Hocking 1997;Pacin et al 2002;Makun et al 2007;Maheshwar et al 2009). In fact, Park et al (2005) found F. proliferatum as the most frequent Fusarium spp.…”
Section: Discussionmentioning
confidence: 86%
“…and several related species contaminate and produce Fumonisins in rice and other stored food products like corn, wheat, asparagus, cowpeas, maize, sorghum, millet, farro, black tea, beer etc. (Kushiro et al 2008(Kushiro et al , 2009Maheshwar et al 2009;Karthikeyan et al 2011;Seefelder et al 2002). Fumonisins are a series of structurally related sphingosine analog toxins (Shier 1992), the most abundant and one of the most active members of this series is Fumonisin B1 (FB1) (Abbas et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxin contamination in foods and feedstuffs poses serious health hazard to animals and humans (Mokhles et al, 2007;Iheshiulor et al, 2011). Mycotoxins are commonly produced by species of Aspergillus, Penicillium and Fusarium (Chandra and Sarbhoy, 1997;Masheshwar et al, 2009). Several strategies are used at controlling fungal growth and the mycotoxin biosynthesis in seeds, grains and feedstuff by chemical treatments, and food preservatives, by physical and biological methods.…”
Section: Introductionmentioning
confidence: 99%